Sirtuin Family Members Selectively Regulate Autophagy in Osteosarcoma and Mesothelioma Cells in Response to Cellular Stress - Garva, Richa; Thepmalee, Chutamas; Yasamut, Umpa; Sudsaward, Sangkab; Guazzelli, Alice; Rajendran, Ramkumar; Tongmuang, Nopprarat; Khunchai, Sasiprapa; Meysami, Parisa; Limjindaporn, Thawornchai; Yenchitsomanus, Pa-thai; Mutti, Luciano; et al. (Frontiers in Oncology, 2019)
The class III NAD+ dependent deacetylases-sirtuins (SIRTs) link transcriptional regulation to DNA damage response and reactive oxygen species generation thereby modulating a wide range of cellular signalling pathways. Here the contribution of SIRT1, SIRT3 and SIRT5 in the regulation of cellular fate through autophagy was investigated under diverse types of stress. The effects of sirtuins’ silencing on cell survival and autophagy was followed in human osteosarcoma and mesothelioma cells exposed to DNA damage and oxidative stress. Our results suggest that the mitochondrial sirtuins SIRT3 and 5 are pro-proliferative under certain cellular stress conditions and this effect correlates with their role as positive regulators of autophagy. SIRT1 has more complex role which is cell type specific and can affect autophagy in both positive and negative ways. The mitochondrial sirtuins (SIRT3 and SIRT5) affect both early and late stages of autophagy, whereas SIRT1 acts mostly at later stages of the autophagic process. Investigation of potential crosstalk between SIRT1, SIRT3 and SIRT5 revealed several feedback loops and a significant role of SIRT5 in regulating SIRT3 and SIRT1. Results presented here support the notion that sirtuin family members play important as well as differential roles in the regulation of autophagy in osteosarcoma versus mesothelioma cells exposed to DNA damage and oxidative stress, and this can be exploited in increasing the response of cancer cells to chemotherapy.